AN OVERVIEW OF FAMILY COPING MECHANISM IN CARING FOR PATIENTS WITH MENTAL DISORDERS IN THE AREA OF UPT PUSKESMAS TIKUNG LAMONGAN - Endah Sri Wijayanti; Banafsa Safa Ayu Shinta; Iswatun Iswatun (Universitas Airlangga, 2023)
Introduction: Family coping mechanism is a family response in dealing with a problem. Each family has different coping mechanisms according to the family's ability to solve problems. Problems with mental disorders cause crises and pressure for caring families, family members who experience mental disorders so that they can affect family coping mechanisms. This study aims to describe the mechanism of family coping in caring for patients with mental disorders in the UPT Puskesmas Tikung Lamongan area. Methods: The research method uses descriptive with a survey time approach. The population in this study were all families who had family members with mental disorders who were recorded in the medical records of UPT Puskesmas Tikung as many as 84 people. The sample technique used purposive sampling, based on inclusion and exclusion criteria, a sample of 55 respondents was obtained. The instrument in this study used the Coping Health Inventory for Parent (CHIP) questionnaire. Results: The results showed that most families had adaptive coping mechanisms, namely 32 respondents (58.2%) and almost half had maladaptive coping mechanisms, namely 23 respondents (41.8%). Conclusions: This study illustrates that families with mental disorders in the UPT Puskesmas Tikung Lamongan area use good coping in dealing with mental disorders. Families are expected to continue to use adaptive coping in providing support and motivation to family members who experience mental disorders so that they are always routinely taking medication.